Risk Factors of Community-Acquired Pneumonia Among Under-Five Children in a Tertiary Level Hospital in Rajshahi (TAJ: Journal of Teachers Association, 2023)
Introduction: Community-acquired pneumonia (CAP) top the list of causes of under-five children mortality worldwide. Therefore, properly assessing and controlling these risk factors may help decrease the morbidity and mortality in under-five children suffering from CAP in Bangladesh and thereby help improve the quality of life of our future generation.Objective: To assess the risk factors of CAP among under-five children ( 2-59 months ) in a tertiary-level hospital in Rajshahi.Materials and methods: This case-control study was carried out in the Department of Pediatrics and EPI Center of Rajshahi Medical College Hospital, RMCH, from January 2017 to December 2018 to determine the risk factors of CAP among children under five. For this study, 246 children aged two months to 59 months were selected by purposive sampling. One hundred twenty-three were cases that were taken indoors, and 123 were healthy controls taken from the outpatient department & EPI center. After taking written consent from guardians, history was taken, and a physical examination was done. All information was recorded in a predesigned data sheet. The chi-square test and odds ratio were used to demonstrate significance.Results: Among 246 children, more patients of both groups were male and came from rural areas. Cases were predominantly under 12 months and came from lower socioeconomic status. A statistically significant association was found between social class and CAP (